Analytical examination of dynamic elements in modern architectural facades for advanced structural aesthetics - Ezz, Mohamed Salah; Odah, Essam; Baharetha, Saleh; Al Sayed, Abd Al-Kader A.; Salem, Doaa A. H. (Frontiers in Built Environment, 2024)
The visual appeal and distinctiveness of a building's external appearance can be enhanced by developing aesthetically pleasing and structurally coherent components, such as diagrids and external bracings, which communicate the building's structural logic. The motivation behind this research is to explore how architectural surfaces can contribute to a building's urban identity by integrating structural systems that are both visually appealing and structurally sound. The hypothesis of this study is that by analyzing and understanding the formal structure, generating diverse patterns, and assessing their impact on stability, it is possible to develop architectural surface components that are aesthetically pleasing and demonstrate proficiency in their application. The research involved analyzing and establishing an informational foundation for architectural projects that address surfaces in alignment with structural connections and various connecting and modulating mechanisms. Specific models of significant architectural achievements from different historical periods were examined to construct a comprehensive knowledge framework. The study resulted in a detailed analytical and descriptive investigation into the intricate mechanisms of form surfaces within Modernity and Deconstruction architecture, and their impact on structural relationships. The research concludes that by integrating structural connections and modulating mechanisms, it is possible to create architectural surface components that enhance a building's visual appeal, artistic expression, and urban identity, while maintaining structural stability and balance.